Magnesium Increases Homoeologous Crossover Frequency During Meiosis in ZIP4 (Ph1 Gene) Mutant Wheat-Wild Relative Hybrids - Rey, María-Dolores; Martín, Azahara C.; Smedley, Mark; Hayta, Sadiye; Harwood, Wendy; Shaw, Peter; Moore, Graham (Frontiers in Plant Science, 2018)
Wild relatives provide an important source of useful traits in wheat breeding. Wheat and wild relative hybrids have been widely used in breeding programs to introduce such traits into wheat. However, successful introgression is limited by the low frequency of homoeologous crossover (CO) between wheat and wild relative chromosomes. Hybrids between wheat carrying a 70Mb deletion on chromosome 5B (ph1b) and wild relatives, have been exploited to increase the level of homoeologous CO, allowing chromosome exchange between their chromosomes. In ph1b-rye hybrids, CO number increases from a mean of 1 CO to 7 COs per cell. CO number can be further increased up to a mean of 12 COs per cell in these ph1b hybrids by treating the plants with Hoagland solution. More recently, it was shown that the major meiotic crossover gene ZIP4 on chromosome 5B (TaZIP4-B2) within the 70Mb deletion, was responsible for the restriction of homoeologous COs in wheat-wild relative hybrids, confirming the ph1b phenotype as a complete Tazip4-B2 deletion mutant (Tazip4-B2 ph1b). In this study, we have identified the particular Hoagland solution constituent responsible for the increased chiasma frequency in Tazip4-B2 ph1b mutant-rye hybrids and extended the analysis to Tazip4-B2 TILLING and CRISPR mutant-Ae variabilis hybrids. Chiasma frequency at meiotic metaphase I, in the absence of each Hoagland solution macronutrient (NH4 H2PO4, KNO3, Ca (NO3)2•4H2O or Mg SO4•7H2O) was analysed. A significant decrease in homoeologous CO frequency was observed when the Mg2+ ion was absent. A significant increase of homoeologous CO frequency was observed in all analysed hybrids, when plants were irrigated with a 1mM Mg2+ solution. These observations suggest a role for magnesium supplementation in improving the success of genetic material introgression from wild relatives into wheat.